2004
DOI: 10.1128/jb.186.24.8301-8308.2004
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Repeat Motifs and Glucan Binding by Glucansucrases of Oral Streptococci and Leuconostoc mesenteroides

Abstract: Glucansucrases of oral streptococci and Leuconostoc mesenteroides have a common pattern of structural organization and characteristically contain a domain with a series of tandem amino acid repeats in which certain residues are highly conserved, particularly aromatic amino acids and glycine. In some glucosyltransferases (GTFs) the repeat region has been identified as a glucan binding domain (GBD). Such GBDs are also found in several glucan binding proteins (GBP) of oral streptococci that do not have glucansucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…In particular, three-dimensional structures in complex with either isomalto-oligosaccharides or dextrans, the natural acceptors of these enzymes, were heavily lacking, thus preventing molecular descriptions of isomalto-oligosaccharide or dextran-binding sites. In particular, no complexes were previously disclosed in which carbohydrates were present in domain V, although this domain was biochemically proven to act as a glucan-binding domain in several GH70 enzymes (25,31,32) and was suggested to participate in the processivity of polymerization (26,28,29). Regarding the ␣-(132) branching sucrase (⌬N 123 -GBD-CD2) enzymes, structural data are even scarcer as only two structures in the apo form have been solved thus far (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, three-dimensional structures in complex with either isomalto-oligosaccharides or dextrans, the natural acceptors of these enzymes, were heavily lacking, thus preventing molecular descriptions of isomalto-oligosaccharide or dextran-binding sites. In particular, no complexes were previously disclosed in which carbohydrates were present in domain V, although this domain was biochemically proven to act as a glucan-binding domain in several GH70 enzymes (25,31,32) and was suggested to participate in the processivity of polymerization (26,28,29). Regarding the ␣-(132) branching sucrase (⌬N 123 -GBD-CD2) enzymes, structural data are even scarcer as only two structures in the apo form have been solved thus far (9).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the five repeats found at the C-terminal extremity of the GBD of DsrP glucansucrase are capable of binding the cell surface of Leuconostoc cells (24). Mutagenesis of conserved aromatic or basic residues of the repeats found in Streptococcus downei GtfI was performed and led to a reduction of the glucan binding capability (25). The elimination of some repeats by truncation was also shown to influence transglucosylation, modify glucan binding properties, and affect the polymer size (26 -29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2a). Within these structural motifs, A repeats, usually present in these regions (Janecek et al, 2000;Shah et al, 2004), are found. Moreover, other repeat units found in this type of protein, such as IDGYYFD+N+G (von Eichel-Streiber et al, 1992) and the Y-G repeats (Giffard & Jacques, 1994), are also contained in these structural motifs (Fig.…”
Section: Dsrp C-terminal Region Molecular Modelmentioning
confidence: 99%
“…This region is involved in binding to the glucan in streptococcal and lactobacilli GSs, and has therefore been designated the glucan binding domain (GBD) (Shah et al, 2004;Krajl et al, 2004a). However, there is controversy about its function in Leuconostoc dextransucrases, as although several authors report strong binding of the C-terminal region to dextran (Miller et al, 1986;Funane et al, 1998), other authors are not able to find this interaction (Shah et al, 2004).…”
Section: Introductionmentioning
confidence: 99%